Posição de caixa e o retorno das ações no mercado acionário brasileiro, 1994-2009 - Bittar, Daniel (2010)
This paper proposes through the principles of Corporate Finance and Asset Pricing measure the impact of the level of liquidity of the companies on the expected return of brazilian equities. The basic assumption of this relationship is that the cash position represents a type of risk not captured by other variables. To estimate this risk will be used a multifactor model. The basic model used is the three-factor model of Fama and French, adapted for the inclusion of the cash variable. From the database, it will attempt to estimate the sensitivity of the expected return of brazilian stocks to cash factor.